Studies on life cycle of white stem borer, Scirpophaga fusciflua Hampson under mid hill conditions of Himachal Pradesh - Tandon, Vikas; Srivastava, Ajai (ORYZA-An International Journal of Rice, 2019)
Life cycle of white stem borer, Scirpophaga fusciflua was studied under laboratory conditions at Rice and Wheat Research Centre, Malan, Himachal Pradesh. Though three generations of white stem borer were recorded in the laboratory conditions, only two were observed in field conditions for a period of one year starting from July. The incubation period varied from7.7 to 8.2 days. The female moths on an average laid 58.4 to 65.6 eggs in masses in different generations with pre-oviposition, oviposition and post-oviposition period of 23.8 to 24.1, 24.9 to 26.0 and 6.0 to 6.6 hours, respectively. The mean adult longevity was 2.5 days.